Two-phase extraction, characterization, and biological evaluation of chitin and chitosan from Rhizopus oryzae - Dhanashree B. Gachhi, Basavaraj S. Hungund (Journal of Applied Pharmaceutical Science, 2018)
Chitin is a polysaccharide based on the monomers of N-acetyl-glucosamine and chitosan is a deacetylated form of it. Our study is emphasized on the two-phase extraction of chitin and chitosan from fungus Rhizopus oryzae (NCIM 877) belonging to Zygomycota. Optimization studies such as utilization of carbon source, pH, and biomass were performed and maximum yield of chitosan (0.288 g/l) was obtained after 9 days of incubation. Characterization studies of chitin and chitosan were performed using Fourier transform infrared spectroscopy and X-ray diffraction methods. Studies on the degree of deacetylation, molecular weight, and viscosity for chitin and chitosan were found to be superior in comparison to standard. The anti-bacterial activity of chitosan was evaluated against the test organisms like Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Salmonella typhi. The chitosan demonstrated higher anti-bacterial activity against gram-positive bacteria as compared with gram-negative ones. The extracted chitosan demonstrated anti-oxidant activity between 60% and 80% as evaluated by 2,2-diphenyl-1-picrylhydrazyl scavenging studies.
Keywords: Chitin, chitosan, FTIR, XRD, anti-bacterial activity, anti-oxidant activity.